1996
DOI: 10.1111/j.1476-5381.1996.tb15701.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of cardioprotection by S‐nitrosoglutathione monoethyl ester in rat isolated heart during cardioplegic ischaemic arrest

Abstract: 1 This study was designed (i) to assess the effect of S-nitrosoglutathione monoethyl ester (GSNO-MEE), a membrane-permeable analogue of S-nitrosoglutathione (GSNO), on rat isolated heart during cardioplegic ischaemia, and (ii) to monitor the release of nitric oxide (-NO) from GSNO-MEE in intact hearts using endogenous myoglobin as an intracellular -NO trap and the hydrophilic N-methyl glucamine dithiocarbamate-iron During aerobic reperfusion, denitrosylation of the MbNO complex slowly occurred as shown by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 54 publications
0
25
1
Order By: Relevance
“…Notably, the protection elicited by SNO-MPG was not abrogated by inclusion of the sGC inhibitor ODQ in the incubations ( Figure 2B), indicating no role for classical NO • / cGMP signaling in the mechanism of protection. This result contrasts with previous studies showing that the cardioprotective effect of GSNO was cGMP dependent [31,42]. At 20 μM, the parent thiol of SNO-MPG (i.e.…”
Section: Protection Of Cardiomyocytes Against Hr Injury By Gsno and Scontrasting
confidence: 94%
See 1 more Smart Citation
“…Notably, the protection elicited by SNO-MPG was not abrogated by inclusion of the sGC inhibitor ODQ in the incubations ( Figure 2B), indicating no role for classical NO • / cGMP signaling in the mechanism of protection. This result contrasts with previous studies showing that the cardioprotective effect of GSNO was cGMP dependent [31,42]. At 20 μM, the parent thiol of SNO-MPG (i.e.…”
Section: Protection Of Cardiomyocytes Against Hr Injury By Gsno and Scontrasting
confidence: 94%
“…Low molecular weight SNOs such as GSNO and S-nitroso-cysteine (SNOC) have previously been used as S-nitrosating agents [23,25], and are known to elicit cardioprotection [31], but are pleiotropic in their actions. Therefore, it was hypothesized that administration of a low molecular weight SNO that accumulates preferentially in mitochondria would deliver cardioprotection at low doses.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that nitrosylmyoglobin is formed during perfusion of the intact rat heart with GSNO (18). GSNO is a potent protective agent against reperfusion injury in this model and it is tempting to speculate that myocyte myoglobin may play a role in the release of nitric oxide from GSNO (19,20).…”
Section: Reaction Of Gsno With Deoxyhemoglobinmentioning
confidence: 88%
“…In addition, the nitrated product may prove valuable to the rational design of a new class of mechanism-based, anti-ischemic drugs that mimic the properties of endogenous uric acid. It is possible that a mimic of the nitrated uric acid product could be utilized to alleviate myocardial ischemic syndromes following ischemia/ reperfusion, cardioplegic ischemic arrest, coronary artery thrombosis after thrombolysis, and restenosis after transluminal coronary angioplasty (63,64). The uric acid nitrosation product may play a pivotal role in human pathophysiology by releasing ⅐NO, which could decrease vascular tone and increase tissue blood flow (65,66).…”
Section: Discussionmentioning
confidence: 99%